Cardiorespiratory markers relate to change-of-direction performance during incremental endurance tests and friendly matches in professional male handball players. - Achenbach, L.; Zinner, C.; Zeman, F.; Obinger, M. (International Journal of Sports Physiology and Performance, 2024)
Purpose To compare the standard Yo-Yo intermittent recovery (IR) test and an agility Yo-Yo IR test with a higher number of change-of-direction movements to cardiorespiratory match performance.